Photochromic RAFT reagent helps construct superior photoswitchable fluorescent polymer nanoparticles for rewritable fluorescence patterning and intracellular dual-color imaging. Issue 42 (12th October 2017) - Chen, Jian; Zhong, Weibang; Xue, Mingju; Wang, Hong; Yu, Maolin; Zhang, Peisheng; Yi, Pinggui
Abstract : Photoswitchable fluorescent polymeric nanoparticles with photochromic RAFT chain transfer reagent were synthesized for rewritable fluorescence patterning and intracellular dual color imaging. Abstract : Superior photoswitchable fluorescent polymer nanoparticles (PFPNs) are highly desirable for photo-rewritable data storage and ultrahigh-resolution bioimaging. Herein, 2-(3′, 3′-dimethyl-6-nitrospiro[chromene-2, 2′-indolin]-1′-yl)ethyl 2-(((dodecylthio)-carbonothioyl)thio)-2-methylpropanoate (SPTTC), a novel photochromic spiropyran-based reversible addition–fragmentation chain transfer (RAFT) reagent, and 5-dimethylaminonaphthalene- N -allyl-1-sulfonamide (DNS), the energy-level matched green fluorescent dye, were firstly synthesized. Then, they are used as donor and acceptor of the designed fluorescence resonance energy transfer (FRET) system to help fabricate superior dual-color PFPNs via a simple one-pot RAFT miniemulsion method. Thanks to its multiple merits such as the photochromic property, improved miscibility, and the ability to control polymerization rate, not only did the designed SPTTC provide the PFPNs with superior photoswitchable fluorescence properties such as high energy transfer efficiency (up to 91%), high dual-color contrast (green and red), rapid photoresponsiveness (2–4 min) and outstanding photoreversibility upon irradiation with UV and visible light, but it also endowed PFPNs with controllable molecular weight and narrow polydispersity index (PDI), excellent cell membrane permeability and long-term fluorescence stability. Moreover, the as-prepared PFPNs were successfully used for rewritable fluorescence patterning and intracellular dual-color imaging due to its prominent properties.